The GLIM criteria as an effective tool for survival prediction in gastric cancer patients. Issue 5 (May 2023) - Zheng, Hua-long; Lin, Jia; Shen, Li-li; Yang, Hai-bo; Xu, Bin-bin; Xue, Zhen; Wu, Dong; Huang, Jiao-bao; Lin, Guo-sheng; Zheng, Chao-Hui; Li, Ping; Xie, Jian-Wei; et al.
Abstract: Background: The Global Leadership Initiative on Malnutrition released a new version of the malnutrition criteria (GLIM criteria). To investigate the influence of the GLIM criteria on the long-term efficacy of radical gastric cancer surgery and establish a nomogram to predict the long-term prognosis of patients with gastric cancer. Methods: A retrospective analysis of 1121 patients with gastric cancer in our department from 2010 to 2013 was performed. A nomogram was established to predict overall survival (OS) based on the GLIM criteria. Patients were divided into the low-risk group (LRG) and high-risk group (HRG) based on the established nomogram. Results: Multivariate Cox regression analyses showed that GLIM criteria was an independent risk factor for the 5-year OS (HR = 1.768, Cl:1.341–2.329, p < 0.001). The C index, AUC and Time-ROC of the nomogram were significantly better than that of GLIM criteria and traditional criteria. The 5-year OS of patients receiving adjuvant chemotherapy in the high-risk group was significantly higher than that of patients without chemotherapy (45.77% vs. 24.73%, p < 0.001). Conclusions: The GLIM criteria independently influence the long-term outcome of patients after radical gastric cancer surgery. The established nomogram can predict the long-term survival of patients with gastric cancer, and postoperative adjuvant chemotherapy for HRG can significantly improve the 5-year OS of patients.